Gene Expression Profiles of Circular RNAs and MicroRNAs in Chronic Rhinosinusitis With Nasal Polyps - Yu, Jieqing; Kang, Xue; Xiong, Yuanping; Luo, Qing; Dai, Daofeng; Ye, Jing (Frontiers in Molecular Biosciences, 2021)
Introduction: Chronic rhinosinusitis (CRS) is often classified primarily on the basis of the absence or presence of nasal polyps (NPs), that is, as CRS with nasal polyps (CRSwNP) or CRS without nasal polyps (CRSsNP). Additionally, according to the percentage of eosinophils, CRSwNP can be further divided into eosinophilic CRSwNP (ECRSwNP) and non-ECRSwNP. CRSwNP is a significant public health problem with a considerable socioeconomic burden. Previous research reported that the pathophysiology of CRSwNP is a complex, multifactorial disease. There have been many studies on its etiology, but its pathogenesis remains unclear. Dysregulated expression of microRNAs (miRNAs) has been shown in psoriasis, rheumatoid arthritis, pulmonary fibrosis, and allergic asthma. Circular RNAs (circRNAs) are also involved in inflammatory diseases such as rheumatoid arthritis, septic acute kidney injury, myocardial ischemia/reperfusion injury, and sepsis-induced liver damage. The function of miRNAs in various diseases, including CRSwNP, is a research hotspot. In contrast, there have been no studies on circRNAs in CRSwNP. Overall, little is known about the functions of circRNAs and miRNAs in CRSwNP. This study aimed to investigate the expression of circRNAs and miRNAs in a CRSwNP group and a control group to determine whether these molecules are related to the occurrence and development of CRSwNP. Methods: Nine nasal mucosa samples were collected, namely, three ECRSwNP samples, three non-ECRSwNP samples, and three control samples, for genomic microarray analysis of circRNA and microRNA expression. All of the tissue samples were from patients who were undergoing functional endoscopic sinus surgery in our department. Then we selected some differentially expressed miRNAs and circRNAs for qPCR verification. Meanwhile, GO enrichment analysis and KEGG pathway analysis were applied to predict the biological functions of aberrantly expressed circRNAs and miRNAs based on the GO and KEGG databases. Receiver operating characteristic (ROC) curve analysis and principal component analysis (PCA) were performed to confirm these molecules are involved in the occurrence and development of CRSwNP. Results: In total, 2,875 circRNAs showed significant differential expression in the CRSwNP group. Specifically, 1794 circRNAs were downregulated and 1,081 circRNAs were upregulated. In the CRSwNP group, the expression of 192 miRNAs was significantly downregulated, and none of the miRNAs were significantly upregulated. GO and KEGG analysis showed differential circRNAs and miRNAs were enriched in “amoebiasis,” “salivary secretion,” “pathways in cancer,” and “endocytosis.” Through qRT-PCR verification, the expression profiles of hsa-circ-0031593, hsa-circ-0031594, hsa-miR-132-3p, hsa-miR-145-5p, hsa-miR-146a-5p, and hsa-miR-27b-3p were shown to have statistical differences. In addition, ROC curve analysis showed that the molecules with the two highest AUCs were hsa-circ-0031593 with AUC 0.8353 and hsa-miR-145-5p with AUC 0.8690. Through PCA with the six ncRNAs, the first principal component explained variance ratio was 98.87%. The AUC of the six ncRNAs was 0.8657. Conclusion: In our study, the expression profiles of ECRSwNP and non-ECRSwNP had no statistical differences. The differentially expressed circRNAs and miRNAs between CRSwNP and control may play important roles in the pathogenesis of CRSwNP. Altered expression of hsa-circ-0031593 and hsa-miR-145-5p have the strongest evidence for involvement in the occurrence and development of CRSwNP because their AUCs are higher than the other molecules tested in this study.